1987
DOI: 10.1002/pros.2990110406
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation studies in the rat prostate: II. The effects of castration and androgen‐induced regeneration upon basal and secretory cell proliferation

Abstract: The changes over short and prolonged periods (up to three months) after castration on the proliferative activity of basal and secretory epithelial cells in the rat prostate were studied. Although castration induced widespread apoptosis of the secretory cells, no compensatory hyperplasia of the basal cells in response to this was noted. Instead, observations of the cell kinetics and ultrastructure suggested that both the basal and secretory cells entered a quiescent state as a result of castration. The prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(105 citation statements)
references
References 27 publications
5
97
0
Order By: Relevance
“…Involution of the prostate gland following castration is associated with increased programmed cell death of luminal cells resulting in an approximately 80% loss of prostatic epithelial cells (Coffey et al 1968, Isaacs et al 1992. The glandular atrophy is incomplete, however, and histological findings in this and previous studies indicate that rudimentary glandular structures remain even after prolonged periods of castration (Sinha et al 1981, Evans & Chandler 1987a. These glandular rudiments consist of both luminal and basal cells, with a decreased relative proportion of luminal:basal cells (3:1 as compared with 13:1 in the intact animal).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Involution of the prostate gland following castration is associated with increased programmed cell death of luminal cells resulting in an approximately 80% loss of prostatic epithelial cells (Coffey et al 1968, Isaacs et al 1992. The glandular atrophy is incomplete, however, and histological findings in this and previous studies indicate that rudimentary glandular structures remain even after prolonged periods of castration (Sinha et al 1981, Evans & Chandler 1987a. These glandular rudiments consist of both luminal and basal cells, with a decreased relative proportion of luminal:basal cells (3:1 as compared with 13:1 in the intact animal).…”
Section: Discussionsupporting
confidence: 45%
“…The luminal cells have been reported as the differentiated progeny of basal progenitor cells of the prostate . However, the findings that not all luminal cells die during prostatic involution induced by androgen withdrawal (Sinha et al 1981, Sinha & Bentley 1984, English et al 1987, Evans & Chandler 1987a and that luminal cells proliferate rapidly following re-administration of testosterone (Sinha & Bentley 1984, English et al 1987, Evans & Chandler 1987a, have led to an alternative proposal of cellular hierarchies within the prostate. This model ascribes two separate cell lineages within the prostatic epithelium, a basal cell and luminal cell lineage, each with its own subpopulation of stem cells (Evans & Chandler 1987a,b).…”
Section: Introductionmentioning
confidence: 99%
“…1B). This model is supported by observations that after castration, residual quiescent luminal cells remain in the rodent prostate that have high proliferative activity upon androgen add-back (Evans and Chandler 1987;Tsujimura et al 2002). Immunohistochemical (IHC) studies have also shown that fetal and prepubertal human epithelia appear positive for all cytokeratins, and no intermediate phenotype was seen in situ (Wernert et al 1987;Wang et al 2001).…”
Section: The Prostate Gland and Adult Prostate Stem Cellsmentioning
confidence: 87%
“…Following androgen ablation, 90% of the luminal cells, but only a small percentage of basal cells will undergo apoptosis during the process of regression (English et al, 1987;Evans and Chandler, 1987). Consequently, early studies favored a basal localization of stem cells, as most basal cells are castration resistant.…”
Section: Identification Of Normal Prostate Epithelial Stem Cells In Micementioning
confidence: 99%